1997
DOI: 10.1103/physrevlett.79.2117
|View full text |Cite
|
Sign up to set email alerts
|

Using Ni Substitution and17ONMR to Probe the Susceptibilityχ(q)

Abstract: We present CuO 2 plane 17 O NMR measurements for Ni-substituted YBa 2 Cu 3 O 61y . The Ni moment induces an oscillatory spin density responsible for the broadening of the NMR line. In slightly overdoped y 1 compounds, this broadening scales with the Ni susceptibility. In contrast, such a scaling is not found in underdoped y 0.6 samples. We associate it with the T dependence of the antiferromagnetic staggered spin susceptibility x 0 ͑Q AF ͒ intrinsic to the CuO 2 planes. Discussion with respect to 63 Cu NMR tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
92
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 24 publications
(27 reference statements)
7
92
2
Order By: Relevance
“…Physical predictions for finite doping are made, which are relevant for experiments probing Knight shifts and the order parameter. The intentional doping of antiferromagnetic materials has become a useful tool in order to study the complicated physics in the context of high temperature superconductivity and quantum magnetism [1,2,3,4,5,6]. Large alternating magnetic moments around static nonmagnetic impurities are observed in Knight shift experiments when a uniform field is applied [3,4,5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical predictions for finite doping are made, which are relevant for experiments probing Knight shifts and the order parameter. The intentional doping of antiferromagnetic materials has become a useful tool in order to study the complicated physics in the context of high temperature superconductivity and quantum magnetism [1,2,3,4,5,6]. Large alternating magnetic moments around static nonmagnetic impurities are observed in Knight shift experiments when a uniform field is applied [3,4,5,6].…”
mentioning
confidence: 99%
“…Jm, 74.25.Nf, 75.20.Hr, 75.40.Mg The intentional doping of antiferromagnetic materials has become a useful tool in order to study the complicated physics in the context of high temperature superconductivity and quantum magnetism [1,2,3,4,5,6]. Large alternating magnetic moments around static nonmagnetic impurities are observed in Knight shift experiments when a uniform field is applied [3,4,5,6]. Theoretical studies have shown that vacancies in low-dimensional antiferromagnetic backgrounds give rise to locally enhanced antiferromagnetic correlations [7,8,9,10,11,12,13,14], which strongly depend on the microscopic model and temperature in the low dimensional models.…”
mentioning
confidence: 99%
“…The structure remains orthorhombic and there is essentially no change in the oxygen level nor in the doping level 9,22,23,24,25,26 . Penetration depth measurements, made down to 1.5 K, show that the superconducting condensate density increases progressively as the temperature is lowered 27 .…”
Section: Discussionmentioning
confidence: 91%
“…The sea of spinons which couple to the localised impurity spin is polarised by an external field and leads to a staggered Cu(2) spin polarisation. The polarisation decreases as r −3 with distance from the Ni impurity and the correlation length could be adjusted to reproduce the observed 17 O NMR line broadening 9 . This treatment pertains to underdoped cuprates where there is a pseudo-gap in the spin excitation spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation